Grafting Delays Watermel on Fruit Ripening by Altering Gene Expression of ABA Centric Phytohormone Signaling - Guo, Shaogui; Sun, Honghe; Tian, Jiaxing; Zhang, Guoyu; Gong, Guoyi; Ren, Yi; Zhang, Jie; Li, Maoying; Zhang, Haiying; Li, Haizhen; Xu, Yong (Frontiers in Plant Science, 2021)
Grafting cultivation is implemented world-wide mainly to resist abiotic and biotic stress, and an effective method to improve watermelon production. However, grafting may affect fruit development and quality. In our experiment, pumpkin grafted (PG) watermelon fruits developed slower and the ripening period was extended compared to self grafted (SG) fruits. We found the concentrations of Abscisic acid (ABA) among endogenous phytohormones were dramatically reduced by pumpkin grafting. In order to understand these changes at the gene expression level, we performed a comprehensive analysis of the fruit flesh transcriptomes between PG and SG during fruit development and ripening. Total of 1675 and 4102 deferentially expressed genes (DEGs) were identified between PG and SG. Further functional enrichment analysis revealed that these DEGs were associated with carbohydrate biosynthesis, phytohormone signaling transmission and cell wall metabolism categories. ABA centric phytohormones signaling and fruit quality related genes including ABA receptor, PP2C proteins, AP2-EREBP transcription factors, sucrose transporter and carotenoid isomerase were co-expressed with fruit ripening. These results provide the valuable resource for understanding the mechanism of pumpkin grafting effect on watermelon fruit ripening and quality development.